2011
DOI: 10.1037/a0024179
|View full text |Cite
|
Sign up to set email alerts
|

Therapists' experiences treating Asian American women with eating disorders.

Abstract: How do psychologists treat eating disorders (EDs) and subclinical issues in Asian American women in a culturally competent manner? Disordered eating and body dissatisfaction are so common in women that most therapists work with the issues to some degree, and it is increasingly likely they will see women of color. Asian American women are at significant risk and yet little treatment literature exists. Twelve therapists with experience in ED treatment were interviewed about their work with Asian American women. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 32 publications
3
59
0
Order By: Relevance
“…Despite limitations, this study supports the importance of psychoeducation . Innovative strategies such as the use of fotonovelas and including family members in treatment could reduce stigma and increase support .…”
Section: Discussionsupporting
confidence: 57%
“…Despite limitations, this study supports the importance of psychoeducation . Innovative strategies such as the use of fotonovelas and including family members in treatment could reduce stigma and increase support .…”
Section: Discussionsupporting
confidence: 57%
“…This conceptual distinction between interdependent and independent selfconstrual is consistent with the theoretical underpinning of social cognition (Fiske & Taylor, 2017). In Asian cultures, achieving the cultural expectation of thinness may bring honor to their family (Smart et al, 2011). Our findings provided evidence regarding the influences of sociocultural context in shaping selfschemata.…”
mentioning
confidence: 56%
“…Despite past research finding no differences in levels of body dissatisfaction between Asian American women and their White American peers (Grabe & Hyde, 2006), the collectivistic orientation of Asian women (from Asia) may place greater pressure on them to meet a set of beauty standards that are central in their culture. In fact, some Asian women perceived adhering to their cultural expectation of thinness as bringing honor to their family (Smart, Tsong, Mejía, Hayashino, & Braaten, 2011). Vietnam, like most other Asian countries, is a relatively collectivistic society (Parks & Vu, 1994).…”
Section: Theoretical Perspectivementioning
confidence: 99%
“…Interviews with therapists with experiences in eating disorder treatment among Asian American women found that the stressful process of acculturation played an important role in clients' eating disorder formation (Smart, Tsong, Mejia, Hayashino, & Braaten, 2011). To these Asian American clients, eating disorder behaviors were a way to cope with stresses related to achieving success and cultural dissonance.…”
Section: Culture and Body Image Perceptionsmentioning
confidence: 99%